The Influence of Field Trip on Junior High School Students’ Naturalistic Intelligence and Problem-Solving Skill in Ecosystem Subject (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2019)
Naturalistic intelligence is a part of multiple intelligences, while problem-solving skills are part of higher-order thinking. Both are learning outcomes required to be developed and improved since these competencies were considered poor in Indonesia. The field trip is a learning method that can encourage students to interact directly with the real object in nature. That learning method is expected to improve students’ naturalistic intelligence and problem-solving skills. In this case, this research was conducted to discover the influence of field trip on students’ naturalistic intelligence and problem-solving skills. This research was experimental research using pre-test and post-test design. The eighth-graders of Islamic school (Madrasah Tsanawiyah) Pameungpeuk, Garut, year of 2017/2018 were employed as the respondents. The obtained data were analyzed using the average comparison tests, which were t-test (for parametric data) and Wilcoxon test (for nonparametric data) with α value of 0.05. Based on the analysis, there was a significant difference in students’ natural intelligence with the sign value of 00,05. These results were supported by the percentage of the affective aspect questionnaire in naturalistic intelligence. In problem-solving skills analysis, the test score revealed a significant difference with a signed value of 0.025 even though the results of the questionnaire only showed a slight difference. Therefore, it was concluded that field trip influenced students’ naturalistic intelligence, however, it had no influence on the affective aspect of problem-solving skills, and conversely, it influenced the cognitive aspect of problem-solving skills. The field trip is potential to be an alternative method for the teacher in junior high school to improve naturalistic intelligence and problem-solving skills applied in ecosystem subject.